Does Increasing Immigration Affect Ethnic Minority Groups?. Issue 1 (September 2021) - Li, Danying; Ramos, Miguel R.; Bennett, Matthew R.; Massey, Douglas S.; Hewstone, Miles
Immigration is increasing around the world. Academic work suggests that increasing immigration reduces social cohesion and subjective well-being, but these studies mainly focused on white majority populations. Using the 2002 to 2014 European Social Survey, we analyze data from 5, 149 ethnic minority respondents living in twenty-four European countries. We examine the association between immigration and respondents' well-being, mediated by two critical cognitive mechanisms: perceived discrimination and generalized trust. We find that in the short term, immigration is associated with greater perceived discrimination, which in turn is associated with lower trust and well-being. Over the longer term, though, immigration is associated with lower perceived discrimination from ethnic minorities, yielding greater generalized trust and perceived well-being.